When Cashiers Meet Customers: An Analysis of the Role of Supermarket Cashiers - Rafaeli, Anat (Academy of Management Journal, 1989)
In a qualitative investigation of the role of supermarket cashiers, the influence of management, co-workers, and customers over cashiers was analyzed. Customers had immediate influence over cashiers at the time of job performance; management influence was more legitimate but more remote. The analysis further revealed that cashiers and customers held different views on who had the right to control service encounters and that cashiers employed various strategies to maintain their control of those encounters.